Preparation method of germane-siloxy alkene heterojunction composite material and application of germane-siloxy alkene heterojunction composite material to photoelectric detector and sensor
By preparing the composite composite material of the heresia-silichene Z-type heterogeneous knitting material, the problem of limited light absorption and low electronic cave compound rates in the optoelectronic compounds in the optoelectronic compounds is solved, and the high performance Optical detectors and sensors, especially in lemon yellow detection, show extremely high sensitivity.
Patent Information
- Application Number
- CN202310921831.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-26
- Publication Date
- 2025-01-28
AI Technical Summary
The existing two-dimensional germane and siloxane have problems in optoelectronic devices with limited light absorption range and low photogenerated electron hole recombination rate, resulting in lower performance of optoelectronic devices.
By using polymer -assisted ultrasonic phase peeling technology to prepare less two -dimensional two -dimensional pyrine and siliconne nanim tablets, and build Z -shaped heterogeneous composite materials through the solution assembly method, improve photoelectric transmission characteristics.
The income composite material has good absorption characteristics for the light from the ultraviolet-to the infrared band. It shows the performance of photoelectric chemicals and sensors with power supply and high-sensitivity, especially the detection of lemon yellow has super high sensitivity.
Smart Images

Figure CN119370799A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a preparation method of a germane-siloxane heterojunction composite material and its application in photoelectric detectors and sensors. The germane-siloxane heterojunction composite material has important application prospects in photoelectric detectors and photoelectric sensors, and belongs to the field of nanocomposite materials and the technical field of photoelectric devices and sensors. Background Art
[0002] In recent years, the development of advanced sensing technology has attracted great attention due to its numerous applications in optoelectronic devices, nanotechnology and environmental monitoring. In particular, there is an increasing demand for high-performance photoelectrochemical (PEC) photodetectors and PEC sensors that can achieve self-powering, wide-band response and ultra-high sensitivity. High-performance photodetectors have broad application prospects in imaging, communication, safety detection and other fields. The detection of food additive content is an important part of ensuring food safety. Traditional detection methods such as UV-visible spectrophotometry, high-performance liquid chromatography and gas chromatography have the disadvantages of long reaction time, expensive instruments and equipment, high detection cost consumption, and high requirements for instrument operation technology. Therefore, it is particularly important to find a convenient, accurate and low-cost food safety detection method as an effective regulatory tool.
[0003] Two-dimensional (2D) materials have become promising candidates in the field of advanced optoelectronic materials due to their unique structures and properties. 2D germane and silicene are derivatives of 2D germanene and silicene, both of which are direct bandgap semiconductor materials and show great potential in the fields of photocatalysis, electrochemical energy storage, electronic devices, nonlinear optical devices, photodetectors, and biomedical applications. Nevertheless, 2D germane and silicene still have disadvantages such as limited light absorption range and high recombination rate of photogenerated electrons and holes when used alone, resulting in low performance of optoelectronic devices based on 2D germane or silicene.
[0004] By constructing a van der Waals heterojunction of two or more two-dimensional materials, the photoelectric transmission characteristics of the obtained materials can often be significantly improved, which is beneficial to improving the photoelectric performance of the device. Based on this, we used polymer-assisted ultrasonic liquid phase exfoliation technology to prepare a few-layer two-dimensional germanane nanosheets and siloxene nanosheets, and then assembled the obtained germanane nanosheets and siloxene nanosheets by solution assembly method at different mass ratios. A Z-type heterojunction composite material was constructed. The obtained composite material has good absorption characteristics for light from ultraviolet-visible to near-infrared bands, can be used as an electrode material for photoelectrochemical photodetectors, shows good responsiveness to light in the 365-980nm band, and has self-powered characteristics. At the same time, since the prepared heterojunction composite material has the highest responsiveness to green light in the 520nm band, the photoelectrochemical photodetector prepared with the heterojunction composite material as the photoelectrode can be used as a green light-driven photoelectrochemical sensor, which has ultra-high sensitivity for the detection of lemon yellow, a pigment food additive. The linear detection range of the obtained photoelectrochemical sensor for lemon yellow solution is 1pM-1μM, and the detection limit is 0.3pM. The photoelectrochemical sensor has broad application prospects in the field of low-cost, fast, efficient and high-precision sensors. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a germane-siloxene heterojunction composite material and its application in a photoelectric detector and a sensor, wherein the method for preparing the germane-siloxene heterojunction is divided into the following steps:
[0006] (1) Using ethanol or deionized water as a solvent, a soluble polymer as a surfactant is dissolved in ethanol or deionized water, and then layered germane or siloxane is dispersed in the polymer solution. The dispersion is placed in an ultrasonic cleaner and ultrasonicated for 2-8 hours at a constant temperature of 3-5°C.
[0007] (2) The dispersion after ultrasonic treatment is centrifuged at a speed of 3000-10000 rpm to remove the unpeeled precipitate to obtain a supernatant, and the supernatant is centrifuged at a speed of 12000 rpm to obtain a precipitate of a few-layer germane or siloxane nanosheet. The precipitate is then ultrasonically dispersed in ethanol, and washed and centrifuged three times. It is placed in a vacuum drying oven and vacuum dried at 60° C. for 24 hours to obtain a powder of a few-layer germane or siloxane nanosheet.
[0008] (3) Weighing germanium and siloxane nanosheet powders in different mass ratios, respectively, and ultrasonically dispersing them in ethanol to obtain a uniform solution. Then, the germanium nanosheet solution and the siloxane nanosheet solution in different mass ratios are mixed together, and ultrasonically mixed until the two are uniformly mixed. The mixed solution is centrifuged at 12000 rpm, and the precipitate is placed in a vacuum drying oven and vacuum dried at 60° C. for 24 hours to obtain a germanium-siloxane heterojunction composite material.
[0009] The method for preparing a germane-siloxane heterojunction composite material is characterized in that the solvent in step (1) is ethanol or deionized water, and the soluble polymer is polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA), sodium hydroxymethyl cellulose (CMC), poly (3,4-ethylenedioxythiophene / polystyrene sulfonate) (PEDOT:PSS). When the solvent is deionized water, the polymer used can be any one of the four polymers; and when the solvent is ethanol, the polymer used is one of PVP, PVA and CMC.
[0010] The method for preparing a germane-siloxane heterojunction composite material is characterized in that the temperature condition of ultrasound in step (1) is a constant temperature of 3-5°C, the ratio of polymer to layered germane or siloxane is 1:3-1:10, preferably 1:5; the amount of solvent used is 10-50 mg of layered germane or siloxane per milliliter of solvent;
[0011] The method for preparing the germane-siloxane heterojunction composite material is characterized in that the speed of centrifugation of the dispersion after ultrasonic treatment in step (2) is 3000-10000 rpm.
[0012] The method for preparing a germane-siloxane heterojunction composite material is characterized in that the mass ratio of germane and siloxane nanosheet powder weighed in step (3) is 1:9, 3:7, 1:1, 7:3, 9:1, preferably 3:7 and 1:1.
[0013] The application of the germane-siloxane heterojunction composite material in photoelectric detectors and sensors is characterized in that the application is achieved in the following manner.
[0014] (1) 30 mg of the composite material was ultrasonically dispersed in 2 mL of ethanol, 200 μL of 0.5 wt% Nafion solution was added, mixed evenly and then drop-coated on ITO, and then vacuum dried in a vacuum drying oven at 60 °C for 24 h to obtain a heterogeneous composite material photoelectrode.
[0015] (2) The prepared composite material photoelectrode is used as the working electrode, the platinum electrode is used as the counter electrode, the calomel electrode is used as the reference electrode, and the Na2SO4 solution is used as the electrolyte, and a photoelectrochemical photodetector and a photoelectrochemical sensor are assembled through a three-electrode system.
[0016] The application of the germane-siloxane heterojunction composite material in photoelectric detectors and sensors is characterized in that the electrolyte concentration range of the optoelectronic photodetector and photoelectrochemical sensor assembled in step (2) is 0.1-1M, wherein the electrolyte concentration is preferably 0.5M when used as an optoelectronic photodetector, and the electrolyte concentration is preferably 0.1M when used as a photoelectrochemical sensor.
[0017] The application of the germane-siloxane heterojunction composite material in photoelectric detectors and sensors is characterized in that the photoelectric detector has a light response range of 365-980nm, an optimal response range of 500-650nm, and has good light responsiveness even when no voltage is applied.
[0018] The application of the germane-siloxane heterojunction composite material in photoelectric detectors and sensors is characterized in that the light wavelength range used by the photoelectric chemical sensor is 500-650nm.
[0019] The application of the germane-siloxane heterojunction composite material in photoelectric detectors and sensors is characterized in that the photoelectric chemical sensor has extremely high sensitivity and ultra-low detection limit for detecting lemon yellow, a pigment food additive. The linear response range for the concentration of lemon yellow solution is 1pM-1μM, and the detection limit is 0.3pM. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 SEM image of germane-siloxane heterojunction composite material and its element surface distribution map
[0021] Figure 2 UV-visible absorption spectrum of germane-siloxane heterojunction composite material
[0022] Figure 3 The photoelectrochemical photodetector based on germanium-siloxane heterojunction composite material has a bias voltage of 0V and a power of 118mWcm -2 Photocurrent response diagram under power density
[0023] Figure 4 The photocurrent response of the electrode under different lemon yellow concentrations and the logarithmic scatter plot and fitting line of photocurrent change-lemon yellow concentration are shown in Figure 2.
[0024] Figure 5 Schematic diagram and energy level structure diagram of germane-siloxane heterojunction composite material DETAILED DESCRIPTION
[0025] The following is a further description of the present invention, but does not limit the scope of the present invention.
[0026] Embodiment 1:
[0027] Preparation method of germane-siloxane heterojunction composite material:
[0028] (1) PVP was dissolved in ethanol as a surfactant, and then 400 mg of layered germane and siloxane were dispersed in the polymer solution respectively. The dispersion was placed in an ultrasonic cleaner and ultrasonicated at a constant temperature of 3° C. for 8 h.
[0029] (2) The dispersion after ultrasonic treatment was centrifuged at 3000 rpm to remove the unpeeled precipitate to obtain a supernatant, and then the supernatant was centrifuged at 12000 rpm to obtain a precipitate of few-layer germane nanosheets and a precipitate of siloxane nanosheets. The two precipitates were then ultrasonically dispersed in ethanol, washed repeatedly, centrifuged three times, and placed in a vacuum drying oven, vacuum dried at 60° C. for 24 hours to obtain powders of few-layer germane nanosheets and few-layer siloxane nanosheets.
[0030] (3) Weighing germanium nanosheets and siloxane nanosheet powders at a mass ratio of 3:7, ultrasonically dispersing them into ethanol to obtain a uniform solution. Then, the germanium nanosheet solution and the siloxane nanosheet solution are mixed together. Ultrasonication is performed until the two are uniformly mixed. The mixed solution is centrifuged at 12000 rpm and the precipitate is placed in a vacuum drying oven at 60° C. and vacuum dried for 24 hours to obtain a germanium-siloxane heterojunction composite material.
[0031] Figure 1 The SEM image and element surface distribution map of the germane-siloxane heterojunction composite material prepared under the present conditions are given. It can be seen that the larger germane nanosheets are covered on the surface by the relatively smaller siloxane nanosheets, forming a closely contacted heterostructure. Figure 2 This is the UV-visible absorption spectrum of the germane-siloxane heterojunction composite material. The light absorption range of the visible composite material is from the UV-visible band to the near-infrared band.
[0032] Embodiment 2:
[0033] Photodetector applications of germane-siloxane heterojunction composite materials:
[0034] 30 mg of the composite material was ultrasonically dispersed in 2 mL of ethanol, 200 μL of 0.5 wt% Nafion solution was added, mixed evenly and then drop-coated on ITO, and then vacuum dried in a vacuum oven at 60 ° C for 24 h to obtain a heterojunction composite photoelectrode. The prepared composite photoelectrode was then used as a working electrode, a platinum electrode as a counter electrode, a calomel electrode as a reference electrode, and a 0.5 M Na2SO4 solution as an electrolyte, and assembled into a photoelectrochemical photodetector through a three-electrode system.
[0035] The photoelectric performance of the photodetector was tested using the Chenhua CHI660D electrochemical workstation. Under the conditions of applying bias voltages of 0, 0.3, and 0.6 V, the photoelectrode was irradiated with monochromatic light of different power densities to test its photocurrent response. The monochromatic light sources used were 365, 405, 520, 635, 750, 803, and 980 nm, respectively.
[0036] Figure 3 The photodetection performance of the germane-siloxane heterojunction composite material is shown in Figure 1. -2 Photocurrent response diagram under power density. It can be seen that the photodetector has a good response to all tested light sources in the range of 365-980nm, exhibits excellent self-powered wide-band response characteristics, and has the greatest responsivity to a wavelength of 520nm.
[0037] Embodiment 3:
[0038] Application of photoelectrochemical sensor of germane-siloxane heterojunction composite material:
[0039] 30 mg of the composite material was ultrasonically dispersed in 2 mL of ethanol, 200 μL of 0.5 wt% Nafion solution was added, mixed evenly and then drop-coated on ITO, and then vacuum dried in a vacuum oven at 60 ° C for 24 h to obtain a heterojunction composite photoelectrode. The prepared composite photoelectrode was then used as a working electrode, a platinum electrode as a counter electrode, a calomel electrode as a reference electrode, and a 0.1 M Na2SO4 solution as an electrolyte to assemble a photoelectrochemical sensor through a three-electrode system.
[0040] The detection performance of the photoelectrochemical sensor was tested using a Chenhua CHI660D electrochemical workstation. Under a bias voltage of 0.3 V, the power density was 118 mW cm -2 The photoelectrode was irradiated with light of wavelength 520nm to test the photocurrent response. First, the photocurrent of the electrode was tested after the electrode was immersed in the electrolyte for 10 minutes without adding lemon yellow. Then, the electrolyte was replaced with a solution containing 10% lemon yellow after the photoelectrode was washed with deionized water and dried with nitrogen each time. -12 , 10 -11 , 10 -10 , 10 -9 , 10 -8 , 10 -6 , 10 -4 and 10 -2 M of 0.1 M Na2SO4 solution, and the photocurrent test was carried out after the electrode was immersed for 10 minutes.
[0041] By measuring the changes in photocurrent at different lemon yellow concentrations, the relationship between the photocurrent change and lemon yellow concentration was obtained. Figure 4 The photocurrent response of the electrode under different lemon yellow concentrations and the logarithmic scatter plot of photocurrent change-lemon yellow concentration and the fitted straight line are shown. It can be seen that the photocurrent density increases with the increase of lemon yellow concentration, and for 10 -12 -10 -6 The detection limit calculated by fitting the straight line is 2.97×10 -13 M, about 0.3pM.
[0042] In order to illustrate the excellent photodetection performance of heterojunction composite materials and the excellent detection performance of photoelectrochemical sensors, we measured and analyzed the band structure of the heterojunction, such as Figure 5 As shown, germanium-siloxane is able to form a direct Z-type heterojunction after close contact. The direct Z-type heterojunction has stronger redox ability and higher charge separation ability than the traditional heterojunction, thereby improving the photoelectric and photocatalytic properties. Lemon yellow can be directly oxidized by the photogenerated holes in the valence band of the siloxane nanosheet. Subsequently, the holes are consumed, which suppresses the recombination of photogenerated electrons / holes, resulting in more free electrons accumulating in the conduction band of the germanium nanosheet, and these electrons are transferred to the electrode to produce an increased photocurrent signal. Ultimately, the concentration of lemon yellow can be directly detected by measuring the change in photocurrent.
[0043] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a germane-siloxane heterojunction composite material and its application in photoelectric detectors and sensors, characterized in that: The method for preparing the germane-siloxane heterojunction is divided into the following steps: (1) Using ethanol or deionized water as a solvent, a soluble polymer as a surfactant is dissolved in ethanol or deionized water, and then layered germane or siloxane is dispersed in the polymer solution. The dispersion is placed in an ultrasonic cleaner and ultrasonicated for 2-8 hours at a constant temperature of 3-5°C. (2) The dispersion after ultrasonic treatment is centrifuged at a speed of 3000-10000 rpm to remove the unpeeled precipitate to obtain a supernatant, and the supernatant is centrifuged at a speed of 12000 rpm to obtain a precipitate of few-layer germane or siloxane nanosheets. The precipitate is then ultrasonically dispersed in ethanol, and the washing-centrifugal precipitation is repeated three times, and then placed in a vacuum drying oven, and vacuum dried at 60° C. for 24 hours to obtain a powder of few-layer germane or siloxane nanosheets. (3) Weighing germanium and siloxane nanosheet powders in different mass ratios, respectively, and ultrasonically dispersing them in ethanol to obtain a uniform solution. Then, the germanium nanosheet solution and the siloxane nanosheet solution in different mass ratios are mixed together, and ultrasonically mixed until the two are uniformly mixed. The mixed solution is centrifuged at 12000 rpm, and the precipitate is placed in a vacuum drying oven and vacuum dried at 60° C. for 24 hours to obtain a germanium-siloxane heterojunction composite material.
2. A method for preparing a germane-siloxane heterojunction composite material as claimed in claim 1, characterized in that In step (1), the solvent is ethanol or deionized water, and the soluble polymer is polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA), sodium hydroxymethyl cellulose (CMC), poly (3,4-ethylenedioxythiophene / polystyrene sulfonate) (PEDOT:PSS). When the solvent is deionized water, the polymer used can be any one of the four polymers; and when the solvent is ethanol, the polymer used is one of PVP, PVA and CMC.
3. A method for preparing a germane-siloxane heterojunction composite material as claimed in claim 1, characterized in that The ultrasonic temperature in step (1) is a constant temperature of 3-5°C, the ratio of polymer to layered germane or siloxane is 1:3-1:10, preferably 1:5; the amount of solvent is 10-50 mg of layered germane or siloxane per ml of solvent.
4. A method for preparing a germane-siloxane heterojunction composite material as claimed in claim 1, characterized in that The dispersion after ultrasonic treatment in step (2) is centrifuged at a speed of 3000-10000 rpm.
5. The method for preparing a germane-siloxane heterojunction composite material according to claim 1, characterized in that: In step (3), the weight ratio of germane and siloxane nanosheet powder is 1:9, 3:7, 1:1, 7:3, 9:1, preferably 3:7 and 1:
1.
6. The use of the germane-siloxane heterojunction composite material in photoelectric detectors and sensors as claimed in claim 1, characterized in that: The application is implemented in the following ways: (1) 30 mg of the composite material was ultrasonically dispersed in 2 mL of ethanol, 200 μL of 0.5 wt% Nafion solution was added, mixed evenly and then drop-coated on ITO, and then vacuum dried in a vacuum drying oven at 60° C. for 24 h to obtain a heterojunction composite photoelectrode. (2) The prepared composite material photoelectrode is used as the working electrode, the platinum electrode is used as the counter electrode, the calomel electrode is used as the reference electrode, and the Na2SO4 solution is used as the electrolyte to assemble a photoelectrochemical photodetector and a photoelectrochemical sensor through a three-electrode system.
7. The application of the germane-siloxane heterojunction composite material in photoelectric detectors and sensors as claimed in claim 5 is characterized in that: The electrolyte concentration of the optoelectronic photodetector and photoelectrochemical sensor assembled in step (2) ranges from 0.1 to 1 M, wherein the electrolyte concentration is preferably 0.5 M when used as an optoelectronic photodetector, and preferably 0.1 M when used as a photoelectrochemical sensor.
8. The application of the germane-siloxane heterojunction composite material in photoelectric detectors and sensors as claimed in claim 5 is characterized in that: The photodetector has a light response range of 365-980nm, an optimal response range of 500-650nm, and has good light responsiveness even without applied voltage.
9. The application of the germane-siloxane heterojunction composite material in photoelectric detectors and sensors as claimed in claim 5 is characterized in that: Photoelectrochemical sensors use light wavelengths in the range of 500-650nm.
10. The application of the germane-siloxane heterojunction composite material in photoelectric detectors and sensors as claimed in claim 5 is characterized in that The photoelectric chemical sensor has extremely high sensitivity and ultra-low detection limit for the detection of lemon yellow, a pigment food additive. The linear response range to the concentration of lemon yellow solution is 1pM-1μM, and the detection limit is 0 3pM.